Удосконалення технологій м'ясо-рибних напівфабрикатів - Пасічний, Василь Миколайович; Степаненко, Інна Олександрівна; Міщук, М. Ю.; Макарчук, Мирослава Ростиславівна; Вишнивенко, Сніжана Валеріївна; Петрусь, О. С.; Ястреба, Юлія Анатоліївна (My University, 2015)
Проведені дослідження щодо розроблення нових видів м'ясо-рибних напівфабрикатів дозволили розробити нові рецептури м'ясо-рибних бургерів та технологію їх виробництва з використанням рибного гелю на основі нубаса. Визначено, що раціональна частка рибного гелю на основі нубаса в рецептурі м'ясо-рибного напівфабрикатів повинна складати 10-20 %, а загальна частка в складі рецептури рибної сировини - 10-17 %, що дозволяє досягти високих структурно-механічних і функціонально-технологічних показників м'ясорибних півфабрикатів. This paper presents a study on improving the technology of meat and fish products with a combination of white and red broiler meat, fish, vegetable raw fish gel to improve the functional and technological characteristics of the semi-finished products. The technology of production of structured food products is based on the realization of the functional properties of raw ingredients that are in the process stream capable of forming a structured system. To give food suitable consistency, use food additives and fillers bilokvimisni. Materials on formulation development of combined meat and fish semi-finished products based on meat, fish and vegetable raw materials with high technological performance through the use of fish gel. Research on the development of new kinds of meat and fish semi-finished it possible to develop new recipes for meat and fish burgers and technology of their production with the use of fish-based gel of nubas.
Keywords: semi-finished products; м'ясо птиці; рибний гель; альгінати; напівфабрикати; poultry; alginates; fish gel; кафедра технології м’яса і м’ясних продуктів